Utilization of cattle manure and potassium fertilizer on soil potassium availability and yield of cowpea (Vigna unguiculata L. Walp) in rainfed rice - Nourma Al Viandari; Elisabeth Srihayu Harsanti; Edi Supraptomo; Anicetus Wihardjaka (Universitas Sebelas Maret, 2024)
Cowpea (Vigna unguiculata L. Walp), a botanical protein source, exhibits resilience in the face of drought-induced stress on rainfed rice fields, especially in dry season crop patterns. Cowpea growth depends on the availability of nutrients in the soil, including potassium (K). In fact, low K availability (exchangeable K is ≤ 0.04 cmol(+) kg-1) is one of the obstacles in rainfed rice fields, especially in increasing crop yields, including cowpea. Therefore, K supplies from various sources are needed to improve soil and cowpea productivity, such as K fertilizer and manure. This study was carried out to determine the response of nutrient management to increase cowpeas’ yield and exchangeable potassium on rainfed rice fields. The field experiment used a randomized block design, with six replications and six fertilizer management treatments, specifically to control composted cattle manure (CCM), Nitrogen Phosphate Fertilizer (NP), CCM+NP, NPK Fertilizer, and CCM+NPK. The parameters observed include plant height, yield components, seed yield, and exchangeable K. Fertilizer management affects the cowpea yield, yield components, K-Uptake, and exchangeable potassium, with the best treatment depicted as CCM+NPK treatment. Compared to the control, CCM by itself and in combination with inorganic fertilizer increases the kernel yield of cowpea by as much as 54-104%, K uptake as much as 40.9-68.2 kg K/ha, and exchangeable K in soil ranging from 37.8-101.3%. It is indicated that the CCM could supply nutrients, including potassium, to overcome potassium deficiency in rainfed rice fields. Furthermore, applying CCM and cultivating cowpeas in rainfed rice fields during the dry season, with water as a limiting factor, is an appropriate option to enlarge the plant yield.